2016
DOI: 10.17129/botsci.278
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of an extremely logged tree species Guaiacum sanctum L. in the Yucatan Peninsula, Mexico

Abstract: Habitat disturbance in tropical forests has affected the viability of several tree species. In Mexico, populations of Guaiacum sanctum have disappeared in some regions due to a strong habitat reduction which could endanger the genetic diversity and connectivity of remnant populations. In this study, 17 populations from the Yucatán Peninsula were analyzed with seven nuclear microsatellites. Several parameters describing the genetic diversity were estimated. The genetic structure was evaluated using Bayesian clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The resulting network graph represents the populations as nodes (locations or landraces for each one of our analyses), with node size reflecting within‐population genetic variance. Nodes are connected by “edges” (lines) whose length is inversely proportional to the genetic covariance between a pair of nodes, thus reflecting the among‐population component of genetic variation (Dyer and Nason, 2004; Oyama et al, 2016). Only 26 locations and 12 landraces of C. annuum and one C. frutescens populations were included in this analysis; locations and landraces with less than four individuals cannot be analyzed by the program because their within‐population variance and genetic covariances cannot be confidently assessed (Dyer and Nason, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting network graph represents the populations as nodes (locations or landraces for each one of our analyses), with node size reflecting within‐population genetic variance. Nodes are connected by “edges” (lines) whose length is inversely proportional to the genetic covariance between a pair of nodes, thus reflecting the among‐population component of genetic variation (Dyer and Nason, 2004; Oyama et al, 2016). Only 26 locations and 12 landraces of C. annuum and one C. frutescens populations were included in this analysis; locations and landraces with less than four individuals cannot be analyzed by the program because their within‐population variance and genetic covariances cannot be confidently assessed (Dyer and Nason, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The biogeography of the region is not only influenced by the effects of the formation and emergence of the Yucatán Peninsula but also by those related to the geology of and tectonic activity and mountain ranges on the Maya block, between the biogeographic breaks Isthmus of Tehuantepec and Motagua-Polochic-Jocotán fault system (Gutiérrez-García & Vázquez-Domínguez, 2012). Although these geological and topographical features and isolation by mountain ranges in the Maya block surely influenced the evolutionary history of Mesoamerican species (e.g., González et al, 2011; Guevara-Chumacero et al, 2010; Gutiérrez-García & Vázquez-Domínguez, 2012; Jiménez & Ornelas, 2016; Rodríguez-Gómez & Ornelas, 2014; Williford et al, 2016), few studies have included phylogeographies of species with patterns of historical divergence and population genetic differentiation between groups of populations from Chiapas and from the Yucatán Peninsula (Gutiérrez-García & Vázquez-Domínguez, 2012; Licona-Vera et al, 2018b; Ortiz-Rodriguez et al, 2020; Oyama et al, 2016). In these studies, the observed patterns of genetic divergence are consistent with the hypothesis that isolation of the dry Yucatán province by semideciduous tropical rain forest along the Petén region and Chiapas restricted northward gene flow from locations of the Pacific slope in Mexico into the TDF in the extreme NW portion of the Yucatán peninsula (an “ecological barrier”; Licona-Vera et al, 2018b and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, detection of barriers to gene flow were more explorative, but all made a link of identified barriers with habitat fragmentation effects. For instance, for an endangered tropical tree (Guaiacum sanctum) across a fragmented landscape in the Yucatán Peninsula, Oyama et al (2016) detected seven barriers to gene flow, which were associated to habitat fragmentation, although the authors did not discard effects of historical barriers. A similar effect was found for the threatened orchid species Laelia speciosa in the fragmented habitat of the Cuitzeo basin (Rojas-Mendez et al, 2017).…”
Section: Figurementioning
confidence: 99%